Primary care-based prevalence of cutaneous lesions among type 2 diabetes mellitus in urban areas of Belagavi, India - Soumya, Chippagiri; Kambar, Sanjay; Patil, Shivkumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetic complications affects every organ and skin is no exception. Cutaneous signs are extremely valuable to physicians as some alert the diagnosis of diabetes mellitus and reflect on glycemic control and lipid metabolism. To estimate the prevalence of cutaneous lesions in urban areas of Belagavi and to find the associated factors. Methods: Data was collected from type 2 diabetes mellitus patients attending Primary care Urban Health Centre. Current diabetics from the Diabetic Register, maintained in the Urban Health Centres were included, and patients’ medical records were reviewed for information regarding duration, medications and complications of diabetes. Information about socio-demographic profile, general physical examination, systemic and cutaneous examination were recorded using validated, predesigned and pretested proforma. All patients were asked detailed history regarding skin complaints, duration of type 2 diabetes mellitus, family history and treatment of diabetes mellitus. All cases underwent cutaneous examination under natural light. Cases where diagnosis was doubtful were confirmed by the Department of Dermatology at K.L.E.’s Dr. Prabhakar Kore Hospital & Medical Research Centre. Results: Of 180 study participants, average age was 59.88±11.06 years and 74.44% were females. 2.56±0.99 years was the mean duration of diabetes and 89.44% were on oral hypoglycemic agents. Prevalence of cutaneous manifestations was found to 48.88%. The cutaneous lesions were asymptomatic in majority of the participants (48.86%) and progressive 48 (54.5%). Conclusions: Cutaneous manifestation were highly prevalent and requires for the physician to be vigilant.